2022
DOI: 10.1002/jat.4325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of airborne total suspended particles (TSP) and fine particulate matter (PM2.5)‐induced developmental toxicity in zebrafish (Danio rerio) embryos

Abstract: Airborne total suspended particles (TSP) and particulate matter (PM 2.5 ) threaten global health and their potential impact on cardiovascular and respiratory diseases are extensively studied. Recent studies attest premature deaths, low birth weight, and congenital anomalies in the fetus of pregnant women exposed to air pollution. In this regard, only few studies have explored the effects of TSP and PM 2.5 on cardiovascular and cerebrovascular development. As both TSP and PM 2.5 differ in size and composition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…A few studies verified PM 2.5 -induced inhibition of the Wnt/β-catenin pathway (Table S8). It was reported that the Wnt/β-catenin pathway was inhibited in zebrafish embryos exposed to PM 2.5 or EOM. , Current literature has suggested that the Wnt/β-catenin pathway is critical to the differentiation process of cardiomyocytes during cardiac development.…”
Section: The Aop On Pm25 Induced Cardiac Developmental Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies verified PM 2.5 -induced inhibition of the Wnt/β-catenin pathway (Table S8). It was reported that the Wnt/β-catenin pathway was inhibited in zebrafish embryos exposed to PM 2.5 or EOM. , Current literature has suggested that the Wnt/β-catenin pathway is critical to the differentiation process of cardiomyocytes during cardiac development.…”
Section: The Aop On Pm25 Induced Cardiac Developmental Toxicitymentioning
confidence: 99%
“…Numerous studies documented ROS overproduction induced by PM 2.5 exposure (Table S1). After exposure to extractable organic matter (EOM) from PM 2.5 , ROS levels were found to be observably higher in the hearts of zebrafish embryos than those in the controls. , Meanwhile, excessive ROS production was verified in human embryonic stem cells (hESCs) and SD rat whole embryos exposed to PM 2.5 . , Current reports hinted that excessive ROS production could be involved in cardiac malformation by triggering subsequent oxidative stress, ER stress, DNA damage, inflammation, etc.…”
Section: The Aop On Pm25 Induced Cardiac Developmental Toxicitymentioning
confidence: 99%
“…These small organisms have mainly been used to acquire knowledge about embryonic development. For example, the zebrafish ( Danio rerio ) has been applied to study the genetic effects of human diseases and drug screening. The fruit fly ( Drosophila melanogaster ) was extensively used to study genetic mutations, heredity, as well as biological processes, including embryonic development, learning, behavior, and aging. Finally, the nematode Caenorhabditis elegans has been used as a model for research in molecular biology, medicine, pharmacology, and toxicology. …”
Section: Microfluidic Devicesmentioning
confidence: 99%
“…Animal models have demonstrated that exposure to specific doses of PM2.5 during pregnancy and lactation causes oxidative stress in the mother, negatively affecting offspring's the emotional and learning memory abilities. 29 The oxidation product malondialdehyde (MDA) and the antioxidant catalase (CAT) activity are important indicators for evaluating oxidative stress processes. PM2.5 exposure has significantly reduced CAT activity and increased MDA levels in the pregnant rat serum dose-dependently.…”
Section: Mechanisms Associated With Pm25-induced Asdmentioning
confidence: 99%